Good Corporate Governance and Financial Performance: Moderating Effects of Company Size - Della Gracia Yudistya Putri; Supramono (PT Mattawang Mediatama Solution, 2022)
This study aims to determine the effect of components of good corporate governance, namely the size of a board of directors, independent board of commissioners, and audit committee size, on company performance as proxied by ROA with company size as moderating variable. A total of 65 samples were used. The data processing method used in this research is panel data regression analysis and Moderated Regression Analysis (MRA) using Eviews 10 software. The result showed the size of the board of directors and the independent board of commissioners do not affect ROA, and only the audit committee affects ROA. The result also showed company size does not moderate the relationship between the size of the board of directors and the size of the independent commissioners on ROA; company size can weaken the relationship between the size of the audit committee and ROA